2019
DOI: 10.5194/hess-2019-377
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evapotranspiration feedbacks shift annual precipitation-runoff relationships during multi-year droughts in a Mediterranean mixed rain-snow climate

Abstract: Abstract. Focusing on the headwaters of the California's Feather River, we investigated how multi-year droughts affect the water balance of Mediterranean mixed rain-snow catchments. Droughts in these catchments saw a lower fraction of precipitation allocated to runoff compared to non-drought years. This shift in precipitation-runoff relationship was larger in a surface-runoff-dominated than in a subsurface-flow-dominated catchment – 39 % and 18 % less runoff, respectively, for a representative precipitation am… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Although drought is driven mainly by lack of rainfall, other factors (e.g., atmospheric evaporative demand, storage in ice and snow, land use change) can also play a role in the occurrence of hydrological drought (Avanzi et al., 2019; Van Loon & Laaha, 2015). Numerous studies indicate that the projected decrease in precipitation across many regions worldwide, particularly in the subtropics, accompanied by a more general increase in atmospheric evaporative demand and thus evapotranspiration, will likely accelerate the severity of hydrological drought in the coming decades on a global scale (Dai, 2021; Diffenbaugh et al., 2015; Prudhomme et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although drought is driven mainly by lack of rainfall, other factors (e.g., atmospheric evaporative demand, storage in ice and snow, land use change) can also play a role in the occurrence of hydrological drought (Avanzi et al., 2019; Van Loon & Laaha, 2015). Numerous studies indicate that the projected decrease in precipitation across many regions worldwide, particularly in the subtropics, accompanied by a more general increase in atmospheric evaporative demand and thus evapotranspiration, will likely accelerate the severity of hydrological drought in the coming decades on a global scale (Dai, 2021; Diffenbaugh et al., 2015; Prudhomme et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…High PET correlates with a low DRT. This can be attributed to Lake Victoria's natural hydrological cycle, where a high PET yields high precipitation levels and wards off drought; low PET will allow little to no precipitation to reach the basin (Avanzi et al 2019) 2018) also found that more rainfall shortened the ecosystem's DRT. Overall, increasing DDT is the most important factor influencing DRT.…”
Section: Factors Affecting Drtmentioning
confidence: 99%
“…High PET correlates with a low DRT. This can be attributed to Lake Victoria's natural hydrological cycle, where a high PET yields high precipitation levels and wards off drought; low PET will allow little to no precipitation to reach the basin(Avanzi et al, 2019). As noted inSchwalm et al (2017), low SPEI values correlate with a high DRT.…”
mentioning
confidence: 92%